Sulfur-Defect-Induced TiS1.94 as a High-Capacity and Long-Life Anode Material for Zinc-Ion Batteries - Wang, Chunlei; Zhao, Chunyu; Pu, Xiangjun; Zeng, Yubin; Wei, Yingjin; Cao, Yuliang; Chen, Zhongxue (ACS applied materials & interfaces, 2024)
Aqueous zinc-ion batteries (ZIBs) are competitive among the elective candidates for electrochemical energy storage systems, but the intrinsic drawbacks of zinc metal anodes such as dendrites and corrosion severely hinder their large-scale application. Developing alternative anode materials capable of high reversibility and stability for storing Zn2+ ions is a feasible approach to circumvent the challenge. Herein, a sulfur-defect-induced TiS1.94 (D-TiS1.94) as a promising intercalation anode material for ZIBs is designed. The abundant Zn2+-storage active sites and lower Zn2+ migration barrier induced by sulfur defects endow D-TiS1.94 with a high capacity for Zn2+-storage (219.1 mA h g–1 at 0.05 A g–1) and outstanding rate capability (107.3 mA h g–1 at 5 A g–1). In addition, a slight volume change of 8.1% is identified upon Zn2+ storage, which favors a prolonged cycling life (50.3% capacity remaining in 1500 cycles). More significantly, the D-TiS1.94||Zn x MnO2 full battery demonstrates a high discharge capacity of 155.7 mA h g–1 with a capacity retention of 59.8% in 400 cycles. It has been estimated that the high-capacity, low-operation voltage, and long-life D-TiS1.94 can be a promising component of the ZIB anode material family, and the strategy proposed in this work will provide guidance to the defect engineering of high-performance electrode materials toward energy storage applications.